The link between COVID-19 and VItamin D (VIVID): A systematic review and meta-analysis - Bassatne, Aya; Basbous, Maya; Chakhtoura, Marlene; El Zein, Ola; Rahme, Maya; El-Hajj Fuleihan, Ghada (Metabolism, clinical and experimental, 2021)
Disease severity and mortality rates due to COVID-19 infection are greater in the elderly and chronically ill patients, populations at high risk for vitamin D deficiency. Vitamin D plays an important role in immune function and inflammation. This systematic review and meta-analysis assesses the impact of vitamin D status and supplementation on COVID-19 related mortality and health outcomes. We searched four databases until December 18th 2020, and trial registries until January 20th 2021. Two reviewers screened the studies, collected data, assessed the risk of bias, and graded the evidence for each outcome across studies, independently and in duplicate. Pre-specified outcomes of interest were mortality, ICU admission, invasive and non-invasive ventilation, hospitalization, time of hospital stay, disease severity and SARS-CoV-2 positivity. We only included data from peer-reviewed articles in our primary analyses. We identified 31 peer-reviewed observational studies. In our primary analysis, there was a positive trend between serum 25(OH)D level <20 ng/ml and an increased risk of mortality, ICU admission, invasive ventilation, non-invasive ventilation or SARS-CoV-2 positivity. However, these associations were not statistically significant. Mean 25(OH)D levels was 5.9 ng/ml (95% CI [−9.5, −2.3]) significantly lower in COVID-19 positive, compared to negative patients. The certainty of the evidence was very low. We identified 32 clinical trial protocols, but only three have published results to-date. The trials administer vitamin D doses of 357 to 60,000 IU/day, from one week to 12 months. Eight megatrials investigate the efficacy of vitamin D in outpatient populations. A pilot trial revealed a significant decrease in ICU admission with calcifediol, compared to placebo (OR = 0.003), but the certainty of the evidence was unclear. Another small trial showed that supplementation with cholecalciferol, 60,000 IU/day, decreased fibrinogen levels, but did not have an effect on D-dimer, procalcitonin and CRP levels, compared to placebo. The third trial did not find any effect of vitamin D supplementation on COVID-19 related health outcomes. While the available evidence to-date, from largely poor-quality observational studies, may be viewed as showing a trend for an association between low serum 25(OH)D levels and COVID-19 related health outcomes, this relationship was not found to be statistically significant. Calcifediol supplementation may have a protective effect on COVID-19 related ICU admissions. The current use of high doses of vitamin D in COVID-19 patients is not based on solid evidence. It awaits results from ongoing trials to determine the efficacy, desirable doses, and safety, of vitamin D supplementation to prevent and treat COVID-19 related health outcomes. •Patients with COVID-19 tend to have lower 25(OH)D levels than healthy subjects.•There is a trend for a positive association between vitamin D deficiency and COVID health outcomes.•Evidence is limited by low quality studies and possible reverse causality mechanisms.•Calcifediol supplementation might decrease the risk of COVID related ICU admission.